PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Pamungkas Collection Tasikmalaya) - Zamzam Fazrian; Arga Sutrisna; Barin Barlian (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine and analyze the influence of organizational culture and leadership on employee performance (a case study on employees at Pamungkas Collection Tasikmalaya). The method used in this research is causality through a case study approach. With a research sample of 57 employees of Pamungkas Collection Tasikmalaya. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results of the study show that together, Organizational Culture and Leadership have a significant influence on Employee Performance at the Tasikmalaya Pamungkas Collection Employees. Partially, organizational culture has a significant influence on employee performance. Partially, leadership has a significant effect on employee performance at Pamungkas Collection Tasikmalaya employees.